2018
DOI: 10.1080/00016489.2018.1440086
|View full text |Cite
|
Sign up to set email alerts
|

l-N-acetylcysteine protects outer hair cells against TNFα initiated ototoxicity in vitro

Abstract: l-NAC is a promising treatment for protecting auditory HCs from TNFα-induced oxidative stress and subsequent loss via programmed cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Therefore, how to select the effective antioxidant for SSNHL has become a puzzled problem to be solved. N-acetylcysteine (NAC), as a precursor of glutathione (GSH) and a limiting factor in the process of GSH synthesis, is one of the antioxidants commonly used in the inner ear (Duan et al, 2004;Pathak et al, 2015;Tillinger et al, 2018). It has been clinically proven to be effective as a single therapy in the treatment of SSNHL or cisplatin-induced hearing loss (Riga et al, 2013;Chen and Young, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to select the effective antioxidant for SSNHL has become a puzzled problem to be solved. N-acetylcysteine (NAC), as a precursor of glutathione (GSH) and a limiting factor in the process of GSH synthesis, is one of the antioxidants commonly used in the inner ear (Duan et al, 2004;Pathak et al, 2015;Tillinger et al, 2018). It has been clinically proven to be effective as a single therapy in the treatment of SSNHL or cisplatin-induced hearing loss (Riga et al, 2013;Chen and Young, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 It has been demonstrated that in AGA, androgens lead to an increase in sebum, bacteria colonies, and porphyrins in tissues influenced by disease and that antioxidant treatment affords protection against hair loss associated with TNF-α-related inflammation and oxidative stress. 18,19 It has been reported by various studies that fibrosis is associated with TGF-β1 in AGA and that androgens play a role in the regulation of ROS in dermal papilla cells and suppress hair growth by increasing the secretion of TGF-β1. [20][21][22] It has been proposed that in physiological concentrations, DHT leads to markedly increased NO levels in dermal papilla cells and NO may play a part in the pathogenesis of AA (Alopecia Areata) via the increase in oxidative cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…[17,27,28]. In addition to its direct antioxidant effect, L-NAC provides protection for hair cells against TNF-α induced toxicity in OC explants [29]. Furthermore, L-NAC reduces ROS/RNS-induced glutamate excitotoxicity in spiral ganglion cell lines and can protect against both the intrinsic and extrinsic apoptotic pathways following chemical insult in hair cells and auditory nerves.…”
Section: Discussionmentioning
confidence: 99%